2020
DOI: 10.1016/s2352-3018(20)30033-3
|View full text |Cite
|
Sign up to set email alerts
|

Ending the HIV epidemic in the USA: an economic modelling study in six cities

Abstract: Background The HIV epidemic in the USA is a collection of diverse local microepidemics. We aimed to identify optimal combination implementation strategies of evidence-based interventions to reach 90% reduction of incidence in 10 years, in six US cities that comprise 24•1% of people living with HIV in the USA. MethodsIn this economic modelling study, we used a dynamic HIV transmission model calibrated with the best available evidence on epidemiological and structural conditions for six US cities: Atlanta (GA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 45 publications
2
68
0
1
Order By: Relevance
“…At best, models can help understand epidemic drivers, predict and assess intervention impact, and optimally allocate funding. 130 , 131 However, they can also be inaccurate, which can lead to erroneous policy decisions. An analysis of 10 HIV models for South Africa 132 found that all projected lower prevalence compared with a subsequent household survey in 2012 and may have been overly optimistic about the impact of ART on HIV transmission.…”
Section: The Importance Of Epidemiologic Data To Inform Policymentioning
confidence: 99%
See 2 more Smart Citations
“…At best, models can help understand epidemic drivers, predict and assess intervention impact, and optimally allocate funding. 130 , 131 However, they can also be inaccurate, which can lead to erroneous policy decisions. An analysis of 10 HIV models for South Africa 132 found that all projected lower prevalence compared with a subsequent household survey in 2012 and may have been overly optimistic about the impact of ART on HIV transmission.…”
Section: The Importance Of Epidemiologic Data To Inform Policymentioning
confidence: 99%
“…Strategies required for ending the HIV epidemic in Atlanta, where the most vulnerable to HIV infection are young Black MSM will differ from rural US counties hard hit by rising rates of injecting drug use and HIV. 130 , 135 Disparities in health care access by race will continue to fuel disparities in HIV incidence unless directly addressed. 130 Decentralized and integrated HIV prevention and care can increase access to services among underserved populations and provide synergistic benefits.…”
Section: The Importance Of Epidemiologic Data To Inform Policymentioning
confidence: 99%
See 1 more Smart Citation
“…We [BN, CDR] have recently written that for six of the largest US cities comprising nearly 1 in 4 people living with HIV/AIDS in the US, implementing a wide range of interventions to diagnose, treat and protect against infection at even near-ideal levels would fall short of the EHE targets [15]. We excluded contact tracing because of the relatively limited experimental evidence supporting its effectiveness in HIV and the uncertainty regarding the potential scale this type of effort could actually reach.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Table 1 shows a comparison of Harris County with select other EHE priority jurisdictions, in terms of core [ 79 ] and other indicators [ 28 ] from the following areas [ 56 ]: policy and legal, socioeconomic, and service availability. Based on modeled forecasts, EHE scale-up of interventions is likely to be cost-saving in Houston/Harris County similar to other Southern hotspots such as Atlanta, Baltimore, and Miami [ 80 ]. However, augmented scale-up [ 81 , 82 ] and differentiated service delivery [ 83 , 84 ] will be required for optimal results.…”
Section: Lessons and Measures From Houstonmentioning
confidence: 99%